2002
DOI: 10.1079/bjn2001509
|View full text |Cite
|
Sign up to set email alerts
|

Effect of esterified 4-desmethylsterols and -stanols or 4,4′-dimethylsterols on cholesterol and bile acid metabolism in hamsters

Abstract: 4-Desmethylsterols and -stanols reduce plasma total cholesterol (TC) and LDL cholesterol by inhibition of intestinal cholesterol absorption, while the cholesterol-lowering potential of 4,4 0 -dimethylsterols is less well defined. The present study aimed to compare the effects of 4-desmethylsterols, -stanols, and 4,4 0 -dimethylsterols on plasma and hepatic cholesterol, sterol excretion and bile acid metabolism. Male golden Syrian hamsters were fed diets containing 13 g/100 g fat, 0·08 g/100 g cholesterol and 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 52 publications
1
12
2
Order By: Relevance
“…Whereas stearic acid-enriched phytosterol esters fed to hamsters at 5% of the diet lowered non-HDL cholesterol [6], our 2.5% PSE treatments did not lower plasma total, non-HDL, or HDL cholesterol. In contrast, hamsters fed a much lower amount (0.24% of the diet) of phytosterol esters made with unsaturated fatty acids (canola oil) exhibited reductions in plasma non-HDL cholesterol [30,31]. We recently reported that phytosterol esters containing unsaturated fatty acids (oleate) are hydrolyzed in vitro to a much greater extent than phytosterol esters containing saturated fatty acids [22], suggesting that hydrolysis and liberation of free sterol may be important factors in decreasing cholesterol absorption and/or plasma non-HDL cholesterol concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas stearic acid-enriched phytosterol esters fed to hamsters at 5% of the diet lowered non-HDL cholesterol [6], our 2.5% PSE treatments did not lower plasma total, non-HDL, or HDL cholesterol. In contrast, hamsters fed a much lower amount (0.24% of the diet) of phytosterol esters made with unsaturated fatty acids (canola oil) exhibited reductions in plasma non-HDL cholesterol [30,31]. We recently reported that phytosterol esters containing unsaturated fatty acids (oleate) are hydrolyzed in vitro to a much greater extent than phytosterol esters containing saturated fatty acids [22], suggesting that hydrolysis and liberation of free sterol may be important factors in decreasing cholesterol absorption and/or plasma non-HDL cholesterol concentration.…”
Section: Discussionmentioning
confidence: 99%
“…When fed PSE at 2.5% of the diet-assuming approximately 5% hydrolysis and the fact that the sterol moiety is 60% of PSE mass-the maximum amount of free phytosterol liberated from hydrolysis would be equivalent to feeding free phytosterol at 0.075% of the diet. In comparison, feeding 0.24% phytosterol esters made with unsaturated fatty acids [30,31], assuming 90% hydrolysis, would be equivalent to feeding free phytosterol at 0.13% of the diet. If cholesterol-lowering efficacy is indeed dependent on the presence of free phytosterol, then our treatment using stearate esters may have had the disadvantage of resisting hydrolysis and limiting the amount of free phytosterol.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the viscous and highly fermentable DF components, some other constituents of the wholegrain barley products may affect steroid metabolism: phytosterols, tocotrienols and/or a-linolenic aid as shown in several studies (Lupton et al 1994;McIntosh et al 1995;Jadhav et al 1998;Kerckhoffs et al 2002;Moreau et al 2002;Trautwein et al 2002). But concentration of phytosterols is relatively low in barley compared with maize products or maize oil.…”
Section: Discussionmentioning
confidence: 99%
“…The feeding of 30 g barley-bran flour or 3 g barley oil in the daily diet lowered total and LDL-cholesterol in hypercholesterolaemic human volunteers (Lupton et al 1994). In several studies, it was shown that phytosterols also, as the counterparts of cholesterol in man and animals, are able to reduce plasma lipids and to increase cholesterol excretion (Moghadasian, 2000;Kerckhoffs et al 2002;Moreau et al 2002;Trautwein et al 2002). Compared with maize, the phytosterol content of barley is relatively low (Piironen et al 2000).…”
mentioning
confidence: 99%
“…It was reported that the differences between effects of different plant oils on blood lipid profiles may be related to their content of plant sterols [46-49]. Indeed, there has been renewed interest in the cholesterol lowering properties of speciality grains and unprocesses oils rich in plant sterols including amaranth oil [50,51], rice bran oil [52] (Berger et al, submitted), avocado oil [53], extra virgin olive oil [54], macadamian nut [55], and argan oil [56]. …”
Section: Physiological Effects Of Plant Sterolsmentioning
confidence: 99%